Model of market orientation of high-tech firms in Germany: validation study - Jangl, Patrik (Business: Theory and Practice, 2016)
The aim of this validation study was to verify a four-factor model of market orientation on a sample of German high-tech companies in the manufacturing industry. A modified version of the measuring scale (MMOS), composed of twelve items, was used for measurement. The target group consisted of business and marketing managers (N = 374) who recorded their answers on a seven-point Likert scale. The main methods used to achieve the objectives were exploratory and confirmatory factor analyses. Having verified the psychometric properties of the instrument, I proceeded to confirm the hypothesis of a four-factor solution model. Reliability and validity of the measuring instrument was also examined, which allowed a confirmation of the second hypothesis. The research may serve as the evidence of the instrument suitability for measuring market orientation in European cultural conditions. To obtain results from other sectors, the author recommends further research replication using the MMOS instrument.